Queering Title IX: Protecting Transgender and Gender Non-Conforming Students from Discrimination, Harassment, and Violence - Ratajczak, Kathleen (Victims & offenders, 2023)
Transgender and gender non-conforming (TGNC) students have unique barriers to success. One method to reduce these barriers is expanding Title IX protections to TGNC students. We adopt a feminist and queer jurisprudence lens to investigate current Title IX guidance. A content analysis of current guidance reveals that only the initial forms of feminist jurisprudence are present in the early guidance. Later guidance displays harmful distortions of feminist jurisprudence, limiting its ability to effectively protect TGNC students from discrimination. We discuss how recent iterations of feminist and queer jurisprudence would more effectively protect TGNC students from discrimination.